Respectful maternity care among women who gave birth at public hospitals in Hadiya Zone, Southern Ethiopia - Mengistie, Tilahun; Mulatu, Teshale; Alemayehu, Afework; Yadeta, Tesfaye Assebe; Dheresa, Merga (Frontiers in Public Health, 2022)
Background: A compassionate and respectful care during pregnancy and childbirth is one of the essential components of safe motherhood. However, most of the women in developing countries experience disrespectful and abusive maternity care during childbirth. Hence, this study assessed the status of respectful maternity care and associated factors to bridge the gap. Methodology: Facility-based cross-sectional study was conducted among mothers who delivered in public Hospitals in the Hadiya Zone, South Ethiopia from March 01-30, 2020. Data were collected using a pretested questionnaire through face-to-face interviews. Descriptive statistics was computed and multivariable logistic regression was fitted to identify predictors. Adjusted Odds Ratio (AOR) with 95% Confidence Interval was used to show the strength of association and level of significance was declared at P-value <0.05. Result: A total of 451 women were included in the study which yielded a response rate of 98.04%. This study showed that 67.8 % (95% CI: 62.4%-70.8%) of mothers received respectful maternal care. Being married [AOR: 2.17, 95% CI (1.03- 6.93)], residing in urban [AOR: 2.22, 95% CI (1.15-4.32)], Cesarean section delivery [AOR: 2.48, 95% CI (1.03-5.97)], and absence of complications during child birth [AOR: 4.37, 95% CI (1.41-13.56)], were significantly associated with respectful maternity care. Conclusions: Two-third of the mothers in the study area received respectful maternity care when they gave birth at a health facility. Sociodemographic, and obstetrics characteristics of the mothers were associated with respectful maternal care. This finding implicates that health facilities have to devise a mechanism to maximize respectful maternal care.